Analisis Koreografi Tari Tagok Alu Tataruang Patah Tigo - Hindira, Pebbi Ratu (PPSDP Undergraduate Journal of Educational Sciences, 2025)
Tagok Alu Tataruang Patah Tigo Dance is a dance based on one of the cases that are rampant in Indonesia, namely about a woman. This case can affect anyone and anywhere, starting from public places or even in the public realm. This case tends to be experienced by women because these women are often considered weak, often belittled and underestimated, and often experience injustice. The impact of a widow's actions can cause the victim to have mental heart disorders, depression stress, and trauma. so that the victim becomes a closed and lonely person. Here invites women to defend themselves to become strong women who are able to survive and overcome the problems that occur. This dance was created by herself as a choreographer. Tagok Alu Tataruang Patah Tigo Dance has its own uniqueness that is different from other dances, namely a combination of traditional movements and new creations that are combined. This makes this dance very interesting to analyze from a choreographic perspective, and is one of the efforts to preserve dance art through written records of the dance when it was first created. The method used is Moving from Withim. The result of this research is a written record of the analysis of creation, movement of space and time.